Optimizing the Cost of Manufacturing Welded Thermo-resistant Steel Pipes - Lenuța Cîndea (Analele Universităţii "Eftimie Murgu" Reşiţa: Fascicola I, Inginerie, 2017)
The presence of stresses in the pipes of unalloyed and low alloyed steels with characteristics specified elevated temperature (hightemperature) can be put in the pipe-Dent the deformations occurring in the welded parts and the knowledge of their size allows to appreciate the ability of the test structures welded. To remove or reduce residual stresses and consequently to dimensional stabilization of the parts, use the thermal process. Comparisons have been made regarding the dimensional stabilization of the welded assembly by heat treatment of stress relief and dimensional stabilization by means of low frequency mechanical vibrations. Starting from the technological flow, two simulations were performed and the results obtained determined that the processing times were reduced in the case of vibration stabilization. The vibration stabilization system decreases thus reducing the manufacturing costs and consumes only a fraction of the heat demanded by the heat process, being one of the processes used predominantly for large welded assemblies, the intent being capable of being chipped at the place where the process of production.